PERTUKARAN SOSIAL DAN HUBUNGAN KERABAT ANTAR PEDAGANG PAKAIAN BEKAS DI PASAR SENGGOL KOTA DUMAI - Munthe, Tina Lestari; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Senggol Market of Dumai City on Used Clothes Merchant. The purpose of this research is to know the pattern of social exchange in economic relationship between used clothing merchant in Senggol Market of Dumai City. The focus of this research is the economic and social activity between used clothing merchant in Senggol Market of Dumai City. This research was conducted on 8 people from traders, 3 people from toke and 1 person as resource person from market manager of senggol dumai city. So the sample in this study is as much as 12 research subjects. Research instances use observation, interview and documentation. This research uses qualitative analysis technique. The research conducted found that the Economic and Social Activity among Used Clothing Traders in Dumai City explains include: Economic Relationships between Merchants, Economic relationships among traders in the market senggol seen from the pricing by tauke and distribution to traders. Competition and Involvement of Relatives in Economic Activity, competition that occurs among traders there is the involvement of relatives in the economic activity of used clothing merchants. Solidarity and Inter-Traders Interactions Different ethnic, solidarity and interaction among ethnic traders found in the used clothing merchant is in the market senggol seen from the form of participation and care that they do as fellow used clothing merchants. The author concludes in the Inter-Social Relationship Relationship among the Relatives in the snggol market there is a proposition within which is Success Proposition. Success proposition occurs between traders with tauke who are relatives. Where the merchant get a reward greater than the cost given tauke relatives to the trader. Social Exchange Relationship Among Traders in Senggol Market Based on Stimulus Proposition is the merchant taking goods from tauke who are not his relatives he has ever taken the goods before and also because in tauke the stock of the desired goods more available. there is a Value Proposition that the trader can take other goods because kedaan goods taken in kedaan ugly and also because the tauke want to take the item for sale the tauke. Keywords: Social Exchange, Kinship, Social Relations